The Effects of Processing Variables on Resonant Acoustic Mixed Polymer Bonded Explosives - Claydon, Andrew (Cranfield University, 2018)
Poster presented at the 2018 Defence and Security Doctoral Symposium.Polymer Bonded Explosives (PBXs) are composite materials which consist of high explosive crystals bound in a polymer matrix. During manufacture, the crystals are dispersed throughout a liquid prepolymer, which is then cured into a crosslinked elastomeric solid. Dispersion can be achieved with Resonant Acoustic Mixing (RAM), a novel mixing technique which uses a vibrating platform to create longitudinal acoustic pressure waves which agitate the mixture. This work describes the outcomes of a comparison between the effects of different mixing vessel surfaces on process efficiency, and a way in which RAM equipment can be modified to mix PBX samples ‘in-situ’, in their end-use cases.NOTE: This poster is based on preliminary data that has since been superseded, additional details on where to find current work will be included here in due course.
Keywords: 'Resonant acoustic mixing'; 'Polymer bonded explosives'; 'DSDS18 poster'; 'DSDS18'; 'Polymers and Plastics'; 'Defence Studies'